Educating tomorrow's marketers. - Brennan, Ross (Marketing Intelligence and Planning: Volume 28, Edition 7., 2010)
The inspiration for this e-book emerged from the marketing education track of the 2009 annual conference of the Academy of Marketing, hosted by Leeds Metropolitan University. This conference track is always popular and lively, but 2009 was a vintage year, with 36 papers submitted. Such a wealth of material seemed to be a suitable foundation on which to build an e-book dealing with the challenges facing marketing educators at the start of the second decade of the millennium.